Mental Health and Productivity in Software Development: A Study with the Bravo Central Platform - Leme, Nicolas Paes; Arriel, Johny; Garcia, Alessandro; Azevedo, Júlia; Sousa, Theo; Bueno, Luana; Godinho, João; Pereira, Juliana Alves (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2024)
Context: Software developers often experience a lot of pressure, including long work hours, tight deadlines, and high-stakes projects. In this context, the mental health of developers has gained increasing attention. Problem: The advent of remote work and the growing adoption of small and agile teams have introduced a new set of challenges. While remote work can offer flexibility, it can also lead to issues such as isolation, burnout, and difficulties in maintaining work-life balance. Small teams, on the other hand, often have fewer resources and less room for making mistakes. State-of-the-art approaches lack a systematic and organized framework to monitor the mental health and productivity of remote and small teams. Solution: We develop an approach based on the GQM (Goal, Question, Metric) methodology to collect, measure, and monitor metrics associated with mental health and productivity. IS Theory: The research is developed under the theoretical framework of Information Systems (IS) theory, specifically focusing on the dimensions of technology, business, and human aspects. Method: We apply the GQM methodology to define goals, questions, and metrics. Data is gathered through surveys and metric analysis, employing both, quantitative and qualitative analysis. Summary of Results: Our analysis confirmed a positive correlation between mental health and productivity. Additionally, it identifies weaknesses and areas for improvement and leads to the development of action plans. Contributions and Impact in the IS area: This research is valuable to support managers in creating healthier work environments, which is a significant concern in the industry.